Prognosis of Neonatal Arterial Ischemic Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2015)
Investigators from University Children's Hospitals in Bern, Zurich, Aarau, and multiple other centers in Switzerland evaluated prospectively the epidemiology, manifestations, and treatment of all full-term neonates with neonatal arterial ischemic stroke (NAIS) and born 2000-2010.